OPTIMASI PENGECORAN STAYED CABLE BETON JEMBATAN PULAU BALANG - Armen Adekristi; Adi Sutrisno; Dhono Nugroho; Sofyan Ramadhani (Jurnal HPJI (Himpunan Pengembangan Jalan Indonesia), 2021)
Abstract Balang Island Bridge is the second longest cable-stayed bridge in Indonesia. This bridge is planned to have 4 traffic lanes with a total length of 971 m. This paper presents the experience of building the main deck of the Pulau Balang Bridge, starting from the challenges of work and optimization, so that the work sequence on this bridge is the fastest in Indonesia. Concrete job mix, equipment arrangement, form traveler design, and detailed calculations on the construction sequence are critical to the success of this project. This study shows that the optimization carried out in the construction of this bridge can shorten the work cycle, from 14 days to 9 days per segment. Keywords: bridge; cable-stayed; optimization; construction sequence; work cycle.  Abstrak Jembatan Pulau Balang merupakan jembatan stayed cable terpanjang kedua di Indonesia. Jembatan ini direncanakan mempunyai 4 lajur lalu lintas dengan panjang total 971 m. Pada makalah ini disajikan pengalaman pelaksanaan pengecoran main deck Jembatan Pulau Balang, dimulai dari tantangan pekerjaan dan optimasi yang dilakukan, sehingga menjadikannya siklus kerja di jembatan inni menjadi yang tercepat Indonesia. Job mix beton, penempatan alat, desain form traveler, dan perhitungan detail pada urutan konstruksi menjadi kunci suksesnya pekerjaan ini. Studi ini menunjukkan bahwa optimasi yang dilakukan pada pembangunan jembatan ini dapat mempersingkat siklus pekerjaan, dari 14 hari menjadi 9 hari per segmen. Kata-kata kunci: jembatan; jembatan stayed cable; optimasi; urutan kosntruksi; siklus pekerjaan.